New species of lysianassoid Amphipoda (Crustacea) associated with seamounts, marine canyons and cold seeps of New Zealand - Kilgallen, Niamh M. (Zootaxa, 2009)
Lysianassoid amphipods collected from various habitats off the coast of New Zealand were examined. A total of seven species were found, representing five genera from three families. Six of these species are new to science. Such a high proportion of new species indicates that the marine amphipod fauna of New Zealand is still quite poorly known. The new species, Ensayara kermadecensis sp. nov., Ensayara ursus sp. nov., Galathella solivagus sp. nov., Hippomedon iugum sp. nov., Hippomedon hurleyi sp. nov. and Tryphosella moana sp. nov., are described in full.